Pathogenic spectrum and drug resistance of bloodstream infection in patients with acute myeloid leukaemia: a single centre retrospective study - Wu, Han; Li, Manning; Shou, Chunyi; Shi, Fangfang; Song, Xiaolu; Hu, Qingfeng; Wang, Ying; Chen, Yirui; Tong, Xiangmin (Frontiers in Cellular and Infection Microbiology, 2024)
Background Bloodstream infection (BSI) represent a prevalent complication in haematological malignancies (HMs). Typically, Patients with BSI usually undergo empirical treatment pending pathogen identification. The timely and effective management of BSIs significantly influences patient prognosis. However, pathogen distribution in BSIs exhibits regional variation. In this study, we investigated the clinical characteristics, pathogen spectrum, drug resistance, risk factors of short-term prognosis and long-term prognostic factors of acute myeloid leukemia (AML) patients with BSI at Zhejiang Provincal People’s Hospital. Methods From 2019 to 2021, a total of 56 AML patients with BSI were treated in the Department of Haematology at Zhejiang Province People’s Hospital. Data regarding pathogen spectrum and drug resistance were collected for analysis. The patients were stratified into non-survivor cohort and survivor cohort within 30 days after BSI, and the predictors of 30-days mortality were identified through both univariate and multivariate Logistic regression analyses. Furthermore, Kaplan-Meier survival analysis and Cox regression analysis were employed to ascertain the risk factors associated with poor prognosis in AML patients complicated by BSI. Results A total of 70 strains of pathogenic bacteria were isolated from 56 AML patients with BSI. Gram-negative bacteria constituted the predominant pathogens (71.4%), with Klebsiella pneumoniae being the most prevalent (22.9%). Gram-positive bacteria and fungi accounted for 22.9% and 5.7%, respectively. Univariate and multivariate analyses revealed significant differences in total protein, albumin levels, and the presence of septic shock between the non-survivor cohort and the survior cohort 30 days post-BSI. COX regression analysis showed that agranulocytosis duration exceeding 20 days (HR:3.854; 95% CI: 1.451–10.242) and septic shock (HR:3.788; 95% CI: 1.729–8.299) were independent risk factors for poor prognosis in AML patients complicated by BSI. Notably, the mortality rate within 30 days after Stenotrophomonas maltophilia infection was up to 71.4%. Conclusions In this study, Gram-negative bacteria, predominantly Klebsiella pneumoniae, constituted the primary pathogens among AML patients with BSIs. Serum albumin levels and the presence of septic shock emerged as independent risk factors for mortality within 30 days among AML patients with BSI. In terms of long-term prognosis, extended agranulocytosis duration exceeding 20 days and septic shock were associated with elevated mortality rates in AML patients with BSI. Additionally, in our centre, Stenotrophomonas maltophilia infection was found to be associated with a poor prognosis. Early intervention for Stenotrophomonas maltophilia infection in our centre could potentially improve patient outcomes.